WWR OPTIMIZATION FOR VENTILATION AND ENVIRONMENTAL NOISE CONTROL OF TROPICAL DWELLING - Samodra, FX Teddy Badai (ARSITEKTURA, 2018)
In an urban environment, heat and noise are the most important factors affecting the environment in buildings. This study optimizes the WWR (Window to Wall Ratio) as a compromise of the ventilation design and noise control for the Javanese architecture which is the case study of Eco-tropical built environment. The need for openings area has a contradictory behavior between providing the maximum aperture requirements for the wind flow and the minimum aperture area to reduce environmental noise. The location of this study is in the lowland (Surabaya, 0-50 m above mean sea level) and in the highland (Malang, 440-667 m above mean sea level) as the representatives of the tropical environment. Both cities were chosen because of their cultural and architectural similarities. The results of this study indicate that the WWR range of integration of ventilation design needs and noise control are for lowland / daytime is 0.13-100% (survey standard), 0.13-5.24% (WHO standard); for lowland / night is 0-100% (survey standard) and 0-3.24% (WHO standard). Meanwhile, for highland / daytime, the requirement is 0.24-100% (survey standard) and 0.24-70.48% (WHO standard); and for highland / night is 0-100% (for both WHO standard and survey criteria).